1986
DOI: 10.1139/z86-076
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics of an unexploited population of fox squirrels (Sciurus niger)

Abstract: 1986. Demographic characteristics of an unexploited population of fox squirrels (Sciurus niger). Can. J. Zool. 64: 5 12-52 1. Demographic changes in an unexploited population of fox squirrels (Sciurus niger) were studied between 1971 and 1978 on 45.2 ha of upland forest in east-central Illinois. Known numbers of squirrels varied between 69 and 142. Adult squirrels (> 15 months old) comprised >50% of the known population during the study, with annual survival exceeding 60%. Young-ofthe-year made up <20% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In temperate, mixed deciduous forests, densities of eastern grey squirrels ( Sciurus carolinensis Gmelin) and fox squirrels ( Sciurus niger L.) remain relatively stable, or fluctuate annually, and are positively correlated with the size of the previous year's seed (acorn) crop (e.g. Thompson 1978; Nixon, Hansen & Havera 1986; Gurnell 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In temperate, mixed deciduous forests, densities of eastern grey squirrels ( Sciurus carolinensis Gmelin) and fox squirrels ( Sciurus niger L.) remain relatively stable, or fluctuate annually, and are positively correlated with the size of the previous year's seed (acorn) crop (e.g. Thompson 1978; Nixon, Hansen & Havera 1986; Gurnell 1996).…”
Section: Discussionmentioning
confidence: 99%
“…1993). Similarly, the behaviour of resident adult grey squirrels seemed to regulate recruitment, and in turn population density, through interactions with juveniles and subadults (Thompson 1978), while in fox squirrels, recruitment of young improved when female density was reduced (Hansen & Nixon 1985; Nixon et al . 1986).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot rule out large-scale movements by 3 squirrels whose fates were unknown, but the intensity of our monitoring and searching programs led us to conclude that such movements were unlikely to have occurred. Although adult squirrels are capable of moving > 1 krn on occasion (Baumgartner 1943;Adams 1976), most dispersal involves juveniles and subadults (Nixon et al 1974(Nixon et al , 1986Delong 1986). Adams (1976) found that subadults exhibited the largest home ranges, and he attributed this to investigative behavior, possibly in preparation for dispersal.…”
Section: Long-range Movements From and Between Woodlotsmentioning
confidence: 99%
“…Although adult eastern fox squirrels are capable of moving .1 km (Shepherd and Swihart, 1995), most dispersal involves juveniles and subadults (Nixon et al, 1974(Nixon et al, , 1986Koprowski, 1996) during April-May or July-October (Thompson, 1978). These movements twice a year may greatly contribute to expansion of range in southern California.…”
mentioning
confidence: 99%